Improvement of crankshaft MAC protocol for wireless sensor networks: a simulation study - Madina Hamiane; Makiya J. Ahmed (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Due to the dramatic growth in the use of Wireless Sensor Network (WSN) applications ranging from environment and habitat monitoring to tracking and surveillance, network research in WSN protocols has been very active in the last decade. With battery-powered sensors operating in unattended environments, energy conservation becomes the key technique for improving WSN lifetimes. WSN Medium Access Control (MAC) protocols address energy awareness and reduced duty cycles. The focus of this study is to investigate, through simulation, the effect of variations in various factors that influence the performance results of WSNs. Using MiXiM framework with OMNeT++ simulator, this simulation study proposes modifications in Crankshaft MAC protocol in order to improve its performance. The impact of duration and number of slots, degree of connectivity among the nodes, mobility speed and mobility update interval and also, the impact of sending data packets without preambles are investigated. Based on the simulation results, an improved version of the Crankshaft protocol for WSN is suggested and a comparative study of the performances of the original and improved protocol is presented. The results clearly indicate the superiority of the improved protocol over its original version.